ChemInform Abstract: Redox‐Neutral α‐Sulfenylation of Secondary Amines: Ring‐Fused N, S‐Acetals. Issue 52 (29th December 2014) - Jarvis, Claire L.; Richers, Matthew T.; Breugst, Martin; Houk, K. N.; Seidel, Daniel
Abstract Secondary amines react with thiosalicylaldehydes in the presence of catalytic amounts of acetic acid to generate ring‐fused N, S‐acetals in redox‐neutral fashion.